Pelatihan Pemeriksaan Kusta Pada Kader Posyandu Puskesmas Waena Kota Jayapura - Inneke Vivi Sumolang; Astrina Rosaria Indah; William Hendrik Reba (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Morbus Hansen (Leprae, Leprosy) is a chronic infection caused by Mycobacteria leprae (M.leprae) The disease affects the skin, the peripheral nerves and other organs. The rate of new cases of leprosy in Papua province is still high. There is a lack of public knowledge about the course of leprosy, if not treated immediately, can cause inflammation of the skin and nerves which worsened condition. Health cadres need to be trained about leprosy examination. Health cadres can detect leprosy at the nearest posyandu because leprosy is still an endemic disease in Papua. There were twenty-three participants who took part in leprosy examination training for posyandu cadres. The activity was carried out by presenting material about leprosy, discussion and simple procedures for examining leprosy which can be carried out by posyandu cadres.